GAMBARAN SUBJECTIVE WELL-BEING PADA WANITA YANG BERADA PADA TAHAP PASCA MASTEKTOMI KANKER PAYUDARA DAN TIDAK MENIKAH - Widhigdo, Jessica Christina; Erawan, Erlyn (Universitas Katolik Widya Mandala Surabaya, 2018)
It is not easy for a woman to accept and take decision to undergo surgical removal of a breast procedure (mastectomy). Losing one of the most important parts of the body that create a woman can be a traumatic event in life. There are many physically and psychologically changes that a patient felt after mastectomy. The research was conducted in order to find out the subjective well-being of single women with breast cancer after mastectomy. Subjective well-being is defined as the positive evaluation cognitively and affectively toward life experience. This research used a qualitative-inductive through an in-depth interview and observation, involving single women with the age range from 44 to 60 years old who have been diagnosed with breast cancer and undergone a mastectomy procedure within the range of 1-15 years before. Result of the research shows that subjective well-being is found in positive evaluations of their life after mastectomy, such as feeling happiness, satisfaction with life, having positive interpersonal relationship, showing their own capabilities in life, religious experiences, being useful for self and family, and thinking positive thinking. This research found that acceptance is an important key that can affect a person’s positive evaluation toward life. Positive acceptance, social support and effective coping stress can help people to have a positive evaluation about their life.